A regulatory role for TGF-β signaling in the establishment and function of the thymic medulla. - Hauri-Hohl, M; Zuklys, S; Holländer, G; Ziegler, S (2014)
Medullary thymic epithelial cells (mTECs) are critical in establishing and maintaining the appropriate microenvironment for negative selection and maturation of immunocompetent T cells with a self-tolerant T cell antigen receptor repertoire. Cues that direct proliferation and maturation of mTECs are provided by members of the tumor necrosis factor (TNF) superfamily expressed on developing thymocytes. Here we demonstrate a negative role of the morphogen TGF-β in tempering these signals under physiological conditions, limiting both growth and function of the thymic medulla. Eliminating TGF-β signaling specifically in TECs or by pharmacological means increased the size of the mTEC compartment, enhanced negative selection and functional maturation of medullary thymocytes as well as the production of regulatory T cells, thus reducing the autoreactive potential of peripheral T cells.